Strategies for Transformation of Higher Education Towards Enhanced Productivity in Nigeria - The Role of Quality Assurance - Cecilia O., Okoro,; Chigozie N., Aguguam,; Chigozie N., Aguguam, (European Scientific Journal, ESJ, 2017)
This paper x-rayed the importance and linkage of education to the development of the Nigerian society. The quality of tertiary education as a system which serves as a mechanism of advancement in Nigeria is being confronted with the age-long difficulties of limited access, scarce financing, decreasing quality and relevance. The paper examines the rationale for the transformation of tertiary education system towards enhanced standard of education in Nigeria. This entails a shift to a more realistic approach that encourages the involvement of everybody’s effort towards ensuring quality in Nigerian higher education. The concept, role and problems of art teaching and learning, role were discussed. The paper concludes that the state of tertiary education in Nigeria is poor and thus the need for new approaches to be utilised to turn the situation around for better. It thus recommended that there should be a complete overhaul of the mode of instruction, massive investment in infrastructures in higher education.